ASSESMENT OF INFECTIOUS ETHYOLOGY IN SEVERE EXACERBATIONS OF CHRONIC OBSTRUCTIVE PULMONARY DISEASE; RELATIONSHIP WITH RESPIRATORY FAILURE - Angelovska, Irina; Karkinski, Dimitar; Debreslioska, Angela; Grueva-Karanfilova, Ada; Miletic, Milena; Dokic, Dejan (Journal of Morphological Sciences; Vol 4 No 2 (2021): JMS, 2021)
Acute exacerbation of chronic obstructive pulmonary disease (COPD) is a negative event in disease evolution which leads to higher morbidity and mortality of patients. Infectious agents are the main cause of exacerbations and they can be easily obtained using new molecular methods. Our objective was to detect respiratory pathogens in patients hospitalized for severe acute exacerbation of COPD and to analyze their relationship with respiratory failure. We examined sputum from 49 patients (male, n=32) older than 40 years, using multiplex PCR microarray for 34 targets of which 18 bacteria, 9 viruses and 7 markers of antibiotic resistance. Blood gas analyses and other clinical and laboratory measures were provided. Infectious etiology was found in 51% of acute exacerbations in hospitalized patients. Of all sputum samples, influenza A was the most frequently detected respiratory pathogen (n = 9, 18.4%) followed by Haemophilis influenzae (n = 7, 14.3 %). We found a significant negative correlation between the presence of the type of detected pathogens and the level of pCO2 in the blood (r = -0.437; p = 0.029); thus, the higher the level of pCO2, the greater likelihood that it is a bacterial infection. Detection of sputum bacteria in patients with severe acute exacerbation of COPD can be an independent risk factor for acute hypercapnic respiratory failure. Keywords : acute exacerbation, COPD, respiratory pathogens, PCR, blood gas analyses https://doi.org/10.55302/JMS2142103a